IMAGING DIAGNOSIS—NUCLEAR SCINTIGRAPHIC, RADIOLOGICAL, AND PATHOLOGIC CHARACTERISTICS OF METASTATIC PILOMATRICOMA IN A DOG. Issue 6 (9th February 2016) - Ruff, Catherine F.; Lim, Chee Kin; Ramos‐Vara, José A.; Custead, Michelle R.; Parys, Magdalena M.; Poulson, Jean M.; Miller, Margaret A.
Abstract : A 6‐year‐old castrated Goldendoodle dog was presented for left‐sided lameness of 3 weeks' duration. Focal, moderate to marked increased 99m Tc‐methylene diphosphonate ( 99m Tc‐MDP) uptake was detected in the right caudal lung lobe, caudal angle of the left scapula, and the distal aspect of the left femur with whole body bone phase scintigraphy. Radiographs identified a well‐circumscribed, oval‐shaped soft tissue opaque mass in the right caudal lung lobe; a suspect oval‐shaped osteolytic lesion in the proximal third of the left scapula; and an osteolytic lesion in the distal aspect of the left femur. Metastatic pilomatricoma was confirmed histologically at all three sites.